Determinasi Audit Delay pada Perusahaan Healthcare yang Terdaftar di Bursa Efek Indonesia - Dadi Kuswandi; Radi Sahara; Wiarsih Febriani; Erna Kustyarini (Jurnal Aplikasi Perpajakan, 2025)
This study aims to determine and analyze the effect of return on assets, debt to equity ratio, company size, company age, and auditor switching on audit delay in healthcare companies listed on the Indonesia Stock Exchange (IDX). The research method used is a quantitative descriptive method with literature and documentation research methods. The data used is secondary data obtained from the annual reports of healthcare companies listed on the IDX and audited for the 2021-2023 period. The analytical tools used in this study consisted of classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination testing. This study partially showed that return on assets and auditor switching had an effect on audit delay, while debt to equity ratio, company size, and company age had no effect on audit delay. Simultaneously, there is a significant effect between the variables of return on assets, debt to equity ratio, company size, company age, and auditor switching on audit delay in the healthcare sector listed on the IDX for the 2021-2023 period.